Data for Learning : Building a Smart Education Data System - Abdul-Hamid, Husein (Washington, DC: World Bank, 2017)
Data are a crucial ingredient in any successful education system, but building and sustaining a data system are challenging tasks. Many countries around the world have spent significant resources but still struggle to accomplish a functioning Education Management Information System (EMIS). On the other hand, countries that have created successful systems are harnessing the power of data to improve education outcomes.